In vitro Studies of Antibacterial and Antifungal Activity of Novel Substituted Benzimidazole Derivatives - Parthiban, Periyasamy; Saravanakumar, Arthanari; Mohanraj, Subramanian; Kavinkumar, Chellamuthu; Saravanan, Sangeetha; Bharat, Palani; Santhosh, Mohan; Abbinanthan, Murugesan (Trends in Sciences, 2023)
A series of 2-substituted amino-1-(1H-benzo[d]imidazol-1-yl)ethanone was prepared by reacting with benzimidazole and chloroacetyl chloride by stirring method. The resultant compound was dissolved in ethanol and refluxed with aryl/aralkyl amine in the presence of anhydrous potassium carbonate. The tested compounds were evaluated against bacterial agents such as E. coli, P. aeruginosa, K. pneumonia, S. typhi, and S. aureus, amoxicillin has been used as a control drug, and also screened for antifungal activity against C. albicans and A. niger at 50 and 100 mg/mL level, griseofulvin used as control drug. The structure-activity relationship led to the conclusion compound PS3 showed equipotent potent, PS4 showed moderate, and PS2 showed less moderate activity. The aromatic/aliphatic chain containing compounds PS1 and PS5 showed the least activity against all bacteria. Compound PS3, PS4 and PS1 showed better activity against C. albicans at 100 µg/mL concentration. The tested compounds PS1, PS3, PS2 and PS4 showed good activity at 100 µg/mL concentration. The compound PS3 can serve as a lead molecule for further development as a new class of antimicrobial agent. GRAPHICAL ABSTRACT